Inversion of Mine Transient Electromagnetic Data via the PSO-GIS Algorithm From a Conical Source - Jiao, Junjun; Yang, Haiyan; Chen, Zhi; Gu, Yanyan; Liu, Jianpeng (IEEE transactions on geoscience and remote sensing, 2022)
The overlap winding system of coils in a multiturn small loop device in the transient electromagnetic method makes the mutual inductance coefficient large, and the measurement data are seriously affected by the turn-off effect. The conical source has the advantages of low mutual inductance effects and strong secondary fields. This study conducts an inversion of an improved particle swarm optimization (PSO) algorithm for this device. The new PSO algorithm improvement strategy (PSO-GIS algorithm) has the advantages of high success rate of optimization, fast convergence speed, high calculation accuracy, and low calculation elapsed time. The inversion results of the theoretical model and the measured mine data show that the PSO-GIS algorithm does not depend on the initial model setting, and the inversion of the layered full-space geoelectric model has a fast convergence speed and enhanced calculation accuracy. The PSO-GIS algorithm inversion is applied to the measured data of coal mine wells, which can achieve the effect of abnormal separation of roof and floor. The reflection of low-resistivity anomalous bodies is refined, and the drilling verification results agree well with the inversion interpretation. The PSO-GIS algorithm inversion in this article can be applied to the processing of real measured mine data to improve the interpretation effect of full-space inversion of mines.